God's Miserable Army Love, Suffering, and Queer Faith in Radclyffe Hall's The Well of Loneliness - Hill, Emily S. (2016)
Despite the obvious biblical allusions in Radclyffe Hall's The Well of Loneliness (1928), the complex theological questions it raises have largely been overshadowed by criticism that focuses on gender and sexuality. This article will read the protagonist, Stephen Gordon, as a queer Christ figure whose suffering ushers in a new ethics of love. Bringing together feminist, queer, and Christian discourses of love and suffering, this article argues that the queerness of love itself is revealed by its proximity to pain and connection to the unintelligible realm of the spirit. By using the christological narrative as a basis for her text, Hall invites the reader to imagine a theology in which queer love is not only acknowledged but elevated to the status of the divine.